Horizontal to Vertical Spectral Ratio (HVSR) Analysis of the Passive Seismic Data on Alluvial Lithology: An Example from Bandung Basin Rim - Evi Fazriati; Muhammad Randy Azhari; Abdul Hakam; Widya Utama; Yudi Rosandi (Postgraduate, University of Mataram, 2023)
Bandung basin is surrounded by active volcanoes at the center of Western Java region. Soil type of this area consists mostly of volcanic alluvial, formed by the past volcanic activities. At this location, we performed passive seismic surveys to reveal the sedimentary characteristics using a triaxial seismometer, to study the properties which have potential implications on environmental aspects, such as natural disaster mitigation and the city planning. In this work we reported the analysis of three component vibration signals by means of the Horizontal to Vertical Spectral Ratio (HVSR) calculation to identify the sediment thickness through the dominant frequency of the earth vibration. The method signal processing successfully revealed the amplification factor of the area, which is very important to determine the potential ground motion induced disasters. The data was collected using a laboratory developed seismic logging device with sensitivity of 0.28 Â± 5% Vâ‹…s/cm. The signal preconditioning was carried out to shape the acquired signals with high noise level, prior to the HVSR calculation. From the measurements and computation, we obtained the thickness variation at the chosen survey area of around 32 to 64 meters, corresponding to the measured dominant frequency of around 2.5 to 5.0 Hz. The results agree very well with the reference sediment thickness measured by the microtremor surveys. The vibration frequencies are also consistent with the range suggested by the literature